Aptamer-based Theranostics in Oncology: Design Strategies and Limitations - Jyoti Trivedi; Mohammad Yasir; Rahul K. Maurya; Alok Shiomurti Tripathi (BIO Integration, 2024)
Cancer remains a major global health burden, necessitating innovative approaches for improved diagnosis and treatment. Aptamer-based theranostics have gained attention in the field of cancer research and treatment. Aptamers can be used as targeting ligands for the delivery of therapeutic agents to cancer cells, as well as for the detection and imaging of cancer, due to high binding affinity and selectivity. Aptamers are also being investigated as anticancer drugs. Specifically, aptamers serve as a tool for controlling protein activity via protein-protein and protein-ligand interactions. The aptamer-exosome technology improves aptamer targeting. To gather relevant data, we searched scientific databases, including PubMed/Medline, Google Scholar, Wiley, Web of Science, and Springer. Despite challenges, theranostics, environmental monitoring, biosensing, and other fields could benefit from the use of aptamer technology. This review discusses the standard methods for producing aptamers, including green aptamers, and potential applications in diagnostics. Aptamers are useful in biotherapy and as anticancer drugs, and this article gives a thorough overview of both with examples. We also covered aptamer-exosome technologies, aptasensors, and their diagnostic and therapeutic applications. We investigated recent systematic evolution of ligands by exponential enrichment (SELEX) methodologies with a focus on carrier materials and technical advances, and discuss the difficulties in creating aptamers that are more practical, highly efficient, and stable.